2021
DOI: 10.1371/journal.pone.0262090
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarettes use among university students in Jordan: Perception and related knowledge

Abstract: The use of e-cigarettes has been increasing in popularity among people, especially young adults. Assessing young individuals’ perceptions of e-cigarettes can help to identify factors that may influence their decision to use e-cigarettes. To examine prevalence, perceptions, and knowledge of e-cigarettes among university students in Jordan, an observational cross-sectional study using an online self-administered questionnaire was conducted among students from public and private universities between October 2020 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 51 publications
(62 reference statements)
6
30
2
Order By: Relevance
“…In Jordan, the situation is not ideal regarding university students’ knowledge about and attitudes toward using e-cigarettes. According to a previous study, 60% of university students in Jordan believed that all e-cigarettes contained natural ingredients, 40% of the students agreed that using e-cigarettes is less addictive than using conventional cigarettes, and 30% of them believed that using e-cigarettes is less risky than using conventional cigarettes [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Jordan, the situation is not ideal regarding university students’ knowledge about and attitudes toward using e-cigarettes. According to a previous study, 60% of university students in Jordan believed that all e-cigarettes contained natural ingredients, 40% of the students agreed that using e-cigarettes is less addictive than using conventional cigarettes, and 30% of them believed that using e-cigarettes is less risky than using conventional cigarettes [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the course lectures included information about electronic cigarettes, that content might be not have been sufficient to change students’ perceptions about electronic cigarettes. Previous studies have reported that smokers considered electronic cigarettes to be less harmful than traditional cigarettes and often used them to aid smoking cessation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous surveys, we found that non-medical students have higher rates of nicotine products use than medical students 37 . This may be due to the fact that medical students are more aware of the effects of nicotine on the body after learning extensive knowledge of physiology and pathology 15,18,29 . Noteworthy, the highest rate of using nicotine products was law students.…”
Section: Discussionmentioning
confidence: 99%
“…E-cigarettes are electronic devices that deliver nicotine to the respiratory system by atomizing an aerosol of smoke containing glycerin, propylene glycol, nicotine and other additives through an electric heating element 12 . Since e-cigarettes do not produce tar, carbon monoxide, and carcinogenic ingredients such as aldehydes, acids, and phenols, the use of e-cigarettes can reduce the number of diseases caused by such ingredients [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%